Prevalence of respiratory viral infection in children hospitalized for acute lower respiratory tract diseases, and association of rhinovirus and influenza virus with asthma exacerbations - Jang-Mi Kwon; Jae Won Shim; Deok Soo Kim; Hye Lim Jung; Moon Soo Park; Jung Yeon Shim (Korean Pediatric Society, 2014)
PurposeIn this study, we aimed to investigate the prevalence of year-round respiratory viral infection in children with lower respiratory tract infection (LRTI) and the relationship between respiratory viral infection and allergen sensitization in exacerbating asthma.MethodsWe investigated the sources for acute LRTIs in children admitted to our hospital from May 2010 to April 2011. The 6 most common respiratory viruses were isolated from nasopharyngeal aspirate using multiplex reverse transcription-polymerase chain reaction in 309 children; respiratory syncytial virus (RSV), adenovirus (AV), parainfluenza virus (PIV), influenza virus (IFV), human metapneumovirus (hMPV), rhinovirus (RV). Atopic sensitization was defined if more than 1 serum specific Immunoglobulin E level measured using UniCAP (Pharmacia) was over 0.35 IU/mL.ResultsRSV was the most common pathogen of bronchiolitis in hospitalized children through the year. RV or IFV infection was more prevalent in asthma exacerbations compared to other LRTIs. AV and hMPV were more likely to cause pneumonia. RV and IFV were associated with asthma exacerbations in children with atopic sensitization, but not in nonatopic children.ConclusionRV and IFV are associated with hospitalization for asthma exacerbation in children with atopic sensitization.